Enhanced recovery after surgery in emergency resection for obstructive colorectal cancer: a systematic review and meta-analysis - Varut Lohsiriwat (2020)
© 2020, Springer-Verlag GmbH Germany, part of Springer Nature. Purpose: Enhanced recovery after surgery (ERAS) improves outcomes after elective colorectal operations. Whether it is beneficial for emergency colorectal surgery is unclear. This study aimed to systematically review and summarize evidence from all studies comparing ERAS versus conventional care in patients having emergency colectomy and/or proctectomy for obstructive colorectal cancer. Methods: EMBASE, MEDLINE, and PUBMED from 1981 to December 2019 were systematically searched. Any studies comparing our primary outcome of interest (length of hospitalization) among patients having emergency resection for obstructive colorectal cancer who received ERAS versus conventional care were selected. Primary outcome was length of hospitalization. Secondary outcomes were gastrointestinal recovery, postoperative complication, 30-day readmission and mortality, and time to start adjuvant therapy. Results: Three cohort studies with 818 participants (418 received ERAS and 400 received conventional care) were included. Length of hospitalization (mean reduction 3.07 days; 95% CI, − 3.91 to − 2.23) and risk of overall complication (risk ratio 0.78; 95% CI, 0.63 to 0.97) were significantly lower in ERAS than in conventional care. ERAS was also associated with quicker time to gastrointestinal recovery, a lower incidence of ileus, and a shorter interval between operation and commence of adjuvant chemotherapy. There was no significant difference in the rates of anastomotic leakage, surgical site infection, reoperation, readmission, and mortality within 30 days after surgery between groups. Conclusions: ERAS had advantages over conventional care in patients undergoing emergency resection for obstructive colorectal cancer—including a shorter length of hospitalization, a lower incidence of overall complication, and a quicker gastrointestinal recovery.